Has the Euro increased Trade? - Maurice J.G. Bun; Franc J.G.M. Klaassen (Tinbergen Institute, 2002)
A major economic reason for the introduction of the euro was its supposedly positive effect on intra-EMU trade. Existing studies examine this suspicion indirectly using non-EMU data and report ambiguous results. We estimate the euro-effect directly from data that include EMU observations. Using a dynamic panel model for annual bilateral exports, we find that the euro has significantly increased trade, with an effect of 4% in the first year and cumulating to around 40% in the long-run. These estimates can be useful in the debates on whether to join the euro in countries such as the U.K.
Keywords: C23; F15; F33; 330; Currency union; dynamic panel data model; EMU; exports; imperfect substitutes model.; Eurozone; Euro; Internationale Wirtschaft; Panelforschung; EU-Staaten